Web 2.0 in restaurants : insights regarding TripAdvisor’s use in Lisbon - Saraiva, João Pedro de Pinho Marques (2013)
TripAdvisor is a Web 2.0 platform that gathers information about restaurants, hotels and sightseeing spots, generated by users for users. It also has an application for mobile devices, which allows users to know what they desire at anytime, anywhere, increasing their user experience (Lugano 2008). This dissertation is focused on the use of this platform by restaurants and users. As so, theoretical concepts like Web 2.0, User-Generated Content, Mobile Social Network, Electronic Word of Mouth and Mobile Marketing are studied in order to know whether or not TripAdvisor is being used and, if positive, in what conditions. With these theories in mind, a dissertation model is created. Thus, willing to know whether or not Lisbon restaurants and users of TripAdvisor are taking advantage of this platform (i.e. answer the research question), several secondary questions arise. These are answered by the nine hypotheses generated, which are based on the model’s goals. Subsequently, in order to collect information from restaurants and users that can verify or not the hypotheses, two surveys are created. Intermediary conclusions that aim to validate each hypothesis are drawn from the results obtained. When analysing these intermediary conclusions, the results show two different answers to the research question. On one hand, restaurants are taking advantage from TripAdvisor’s platform, even if they are not using all the capacities offered. On the other hand, Lisbon users are not yet taking benefits from this platform. This inconsistency can be explained due to the fact that restaurants centre TripAdvisor around tourists and Lisbon habitants use it outside of Lisbon while travelling. Thus, Lisbon citizens do not use this platform on a daily basis: they do it while visiting other cities. In comparison, Lisbon restaurants use this platform in order to attract tourists, which mean that they are taking advantage of TripAdvisor but not from Lisbon users.